Inversion breakpoints and the evolution of supergenes. Issue 12 (28th April 2021) - Villoutreix, Romain; Ayala, Diego; Joron, Mathieu; Gompert, Zachariah; Feder, Jeffrey L.; Nosil, Patrik
Abstract: The coexistence of discrete morphs that differ in multiple traits is common within natural populations of many taxa. Such morphs are often associated with chromosomal inversions, presumably because the recombination suppressing effects of inversions help maintain alternate adaptive combinations of alleles across the multiple loci affecting these traits. However, inversions can also harbour selected mutations at their breakpoints, leading to their rise in frequency in addition to (or independent from) their role in recombination suppression. In this review, we first describe the different ways that breakpoints can create mutations. We then critically examine the evidence for the breakpoint‐mutation and recombination suppression hypotheses for explaining the existence of discrete morphs associated with chromosomal inversions. We find that the evidence that inversions are favoured due to recombination suppression is often indirect. The evidence that breakpoints harbour mutations that are adaptive is also largely indirect, with the characterization of inversion breakpoints at the sequence level being incomplete in most systems. Direct tests of the role of suppressed recombination and breakpoint mutations in inversion evolution are thus needed. Finally, we emphasize how the two hypotheses of recombination suppression and breakpoint mutation can act in conjunction, with implications for understanding the emergence of supergenes and their evolutionary dynamics. We conclude by discussing how breakpoint characterization could improve our understanding of complex, discrete phenotypic forms in nature.